Hyperaldosteronism due to unilateral adrenal hyperplasia - Mendoza-Montoya, Liz Kathia (2019)
This is the case of a 56 year-old male patient who attended at endocrinology clinic for the study of resistant hypertension and symptomatic recurrent hypokalemia, who underwent surgery with the presumptive diagnosis of adrenal adenoma but the histopathological study showed an unilateral macronodular adrenal hyperplasia.